Desacralization of Catus Patha in Bali Hinduism Community - I Wayan Wastawa; I Ketut Sudarsana (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
The article aims to analyze the desacralization of the symbol of Catuspatha. Catuspatha is a form of Pakraman village identity in residential space patterns and as an orientation center of the Pakraman village pattern in Bali. At the same time, a socio-cultural phenomenon arises towards the center of the orientation of the Balinese society today, namely the replacement of the Visnu Murti statue with the Bungkarno statue in Catuspatha, Banjar Anyar Village. A ruling elite plays an essential religious symbol. In this case, the researcher analyzed the more fundamental way of shifting the shrine Catuspatha. The problem is that the Hindu community sees an imbalance between expectations and the reality of the existence of Catuspatha, the factors of desacralization of Catuspatha, and the impact of the desacralization of Catuspatha on the beliefs of the people. These problems are analyzed eclectically with religious theory, Social Change, and Deconstruction Theory. Data were obtained through observation, unstructured interviews, and literature studies to obtain objective analysis. The research found that the Catus Patha served as upstream Pakraman Kediri Village because they are still functioned to carry out Ngider ceremonies. The caused desacralization, more dominantly caused by socio-political factors, namely the idea of respect for the services of a warrior by forgetting local competitiveness. While the impact of the desacralization more on the theological impact, namely the weakening of public confidence and trust in the existence of Catuspatha so that the shifting of the Ngider ceremony orientation center is sought.